Manual de patologías de daños y evaluación geo-referenciada de las carreteras de asfalto de la red vial correspondientes a los cantones Machala, Pasaje, Santa Rosa, Huaquillas, el Guabo y Arenillas de la provincia de el Oro” - Mosquera Aráuz, William Andrés (2015)
The absence of a manual pathologies of damage and geo- referenced assessment of asphalt roads cantons : Machala , Pasaje Santa . Rosa , El Guabo , Huaquillas and Arenillas of the province of El Oro, does not provide a suitable technical management on the type and quality of treatments such routes , so that optimal roads are obtained.